Zaskia Putri Nurlita Universitas Jenderal Achmad Yani Yogyakarta - Zaskia Putri Nurlita Amir Fatah (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2026)
Abstract This study aims to examine the effect of the use of the Indonesian Standard Quick Response Code (QRIS) on perceived ease of use, perceived usefulness, risk, financial literacy, and accounting information systems among Micro, Small, and Medium Enterprises (MSMEs) in Sleman Regency. The adoption of digital payment systems, particularly QRIS, has transformed financial transactions and driven the modernization of MSME operations. This study used a quantitative approach by distributing questionnaires to 100 MSMEs in the culinary sector in Sleman Regency. Data analysis was conducted through validity and reliability tests, multiple linear regression, and hypothesis testing to examine the relationships between variables. The results indicate that QRIS use has a positive and significant effect on perceived ease of use, perceived usefulness, and increased financial literacy. However, perceived risk remains a factor that can influence user trust. Furthermore, QRIS implementation can improve the effectiveness of accounting information systems through more efficient transaction recording and management. This study emphasizes the importance of integrating digital payment systems to improve efficiency and financial literacy among MSMEs and provides input for stakeholders in optimizing QRIS implementation.